'And so it is licly to men': Probabilism and Hermeneutics in Wycliffite Discourse. (25th February 2019) - Ghosh, Kantik
Abstract: The Latin sermons of John Wyclif (d.1384), as also the long English cycle of 294 sermons by his followers drawing on his Latin work, show a pervasive, and surprising, use of the labile and contentious medieval discourses related to probable reasoning. This article attempts to examine the implications of such usage in the context of biblical exegesis, polemics and homiletic exhortation. The Wycliffites, like their master, posited as foundational that access to the divine mind via the Bible, independent of the corruptions and concupiscence of a schismatic Church and a vainglorious theological magisterium, was possible and indeed necessary. However, the evidence of these sermons points in a very different direction, and suggests that a deep hermeneutic and epistemological uncertainty, bordering on what is at times a barely averted scepticism, underlay their valiant efforts to apply God's word to human affairs.